Answer:
x² = 4y/3
Step-by-step explanation:
The standard form of the parabola is
![(x-h)^2=4p(y-k)](https://img.qammunity.org/2023/formulas/mathematics/high-school/7n1egla3ro1gayr3wb18awbiroxmb3i8u7.png)
Where (h, k) is the vertex and p is a number determined by the focus because the focus is located (h, k+p).
In this case, (h, k) = (0, 0), so the focus is also equal to
focus = (0, 1/3) = (0, 0 + p)
It means that
1/3 = 0 + p
1/3 = p
Then, replacing (h, k) = (0, 0) and p = 1/3, we get that the equation of the parabola is
![\begin{gathered} (x-0)^2=4((1)/(3))(y-0) \\ x^2=(4)/(3)y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8f6ex5oye4l5wywsf8etfcx4w00pd6m27a.png)
Therefore, the answer is
x² = 4y/3